Evolution of treatment of femoral shaft fracture in polytrauma: Did damage control orthopaedics improve the outcome? A retrospective study. Issue 7 (July 2021) - Feldman, Guy; Mosheiff, Ram; Nasrallah, Khalil; Shabtai, Ran; Davidson, Amit; Weil, Yoram A.
Highlights: The Damage Control Orthopaedics (DCO) approach, is still a matter of debate. This study, retrospectively examines the outcome of the paradigm shift to DCO in our hospital. A total of 96 patients with femoral shaft fractures were evaluated. The authors couldn't demonstrate better outcomes by applying DCO concepts in polytrauma patients. Abstract: Background: Treatment of polytrauma patients with femoral shaft fracture has changed considerably during the past few decades. A transition from early total care (ETC) to "Damage Control" Orthopaedics (DCO) in selected patients was proposed in order to decrease mortality. The aim of the study was to investigate whether this policy change resulted in improved patient outcome. Methods: We present a retrospective, comparative study, held in a Level I trauma center in Jerusalem, Israel. Polytrauma patients with Injury Severity Score higher than 16 with femoral shaft fracture were included. Data was extracted from our institute's electronic trauma registry. The study examines two time periods: Between the years 1996 and 2006 patients were treated according to the ETC protocol, with immediate intramedullary nailing (IMN) within 12 h. From 2007 until 2019 a DCO policy was adopted, implementing temporary external fixator for high risk patients, according to the "Hannover" criteria. Following resolution of the acute phase, these were converted to IMN. Patients eligible for DCO were matched to controls who received ETC during the earlier period. Results: A total of ninety-six patients were included (DCO n  = 44, ETC n  = 52). The groups were comparable in terms of age, gender, mechanism of injury, injury to surgery time and Injury severity score (DCO median 31.5, ETC median 29). No statistical difference was found between the groups in terms of mortality ( P  = 0.757), acute respiratory distress syndrome ( P  = 0.534), sepsis ( P  = 0.519) and hospital stay (DCO median 24 days, ETC median 21.5 days) or ICU stay (Median 7 days in both groups). Conclusions: This pilot study did not demonstrate better outcome by implementing DCO concepts in the polytrauma patient. Level of evidence: III prognostic.